ANALISIS TINGKAT KESEHATAN BANK MENGGUNAKAN METODE CAMEL PADA LAPORAN KEUANGAN PT. BANK SYARIAH INDONESIA TBK TAHUN 2019-2023 - Yuriani, Ima; Andre Agustianto, Mochammad (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
This study was conducted because it is very important for financial institutions to maintain their financial health, especially Islamic banks. The purpose of this study is to determine the health level of PT. Bank Syariah Indonesia (BSI) Tbk in 2019-2023. The assessment indicators used in this study are Capital, Asset Quality, Management, Earning, and Liquidity or abbreviated as CAMEL. The Camel method is a factor that greatly determines the health of a bank. This study was conducted with a quantitative descriptive approach, namely using secondary data obtained from the annual Financial Report published on the company's official website, by analyzing the CAR, NPF, PDN, ROA, ROE, BOPO, NI, and FDR ratios. The results of the study showed that the CAR ratio in the 2019-2023 period received the predicate "very healthy". The NPF ratio for the 2019-2023 period received the predicate "healthy". The PDN ratio for the 2019-2023 period was given the predicate of "fairly healthy". The ROA ratio in 2019-2022 was given the predicate of "healthy", while in 2023 it was given the predicate of "very healthy". The ROE ratio in 2019-2020 was given the predicate of "fairly healthy", while in 2021-2023 it was given the predicate of "healthy". The BOPO ratio in 2019-2023 was given the predicate of "very healthy". The NI ratio in 2019-2023 was given the predicate of "healthy". The FDR ratio in 2019 was given the predicate of "healthy". In 2020-2021 it increased to get the predicate of "very healthy". However, in 2022-2023 it was again given the predicate of "healthy". The findings reveal that, based on these indicators, Bank Syariah Indonesia Tbk's performance between 2019 and 2023 averaged in the "Healthy" category, demonstrating strong financial health according to the overall assessment